2013
DOI: 10.1016/j.foreco.2013.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Floristic composition, species diversity and carbon storage in charcoal and agriculture fallows and management implications in Miombo woodlands of Zambia

Abstract: Globally, there are increasing demands for land use changes aimed at restoring Carbon (C) 5 and biodiversity in degraded forest ecosystems. This study provides an integrated 6 understanding of aboveground (AG) C storage, structural and floristic composition in 7 charcoal and agriculture fallows in Miombo woodland systems of Zambia. We present the 8 findings of ecological surveys; measuring tree diameters and assessing species composition 9 on twenty-four 0.25 ha plots in undisturbed woodlands, and fifty-eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
78
7
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(107 citation statements)
references
References 54 publications
15
78
7
7
Order By: Relevance
“…In Kitulanghalo Forest Reserve and Ihombwa village, Backéus et al [1] and Mbwambo et al [42] found 79 and 86 species, respectively, from Tanzania's Miombo woodland. The average tree density of 517 ± 85 trees/ha in Miombo woodland is comparable with those reported by Backéus et al [1], Campbell et al [2], Kalaba et al [4] and Chidumayo [5].…”
Section: Species Composition and Richnesssupporting
confidence: 87%
See 1 more Smart Citation
“…In Kitulanghalo Forest Reserve and Ihombwa village, Backéus et al [1] and Mbwambo et al [42] found 79 and 86 species, respectively, from Tanzania's Miombo woodland. The average tree density of 517 ± 85 trees/ha in Miombo woodland is comparable with those reported by Backéus et al [1], Campbell et al [2], Kalaba et al [4] and Chidumayo [5].…”
Section: Species Composition and Richnesssupporting
confidence: 87%
“…Miombo woodland is distinguished from other African savanna. In Miombo woodland, woodland and forest are formed by the dominance of tree species in the family Fabaceae, subfamily Caesalpinioideae, particularly in the genera Brachystegia, Julbernardia and Isoberlinia [3,4], while these genera are seldom found outside Miombo [5,6]. Miombo is regarded as a vegetation type that has been used by humans since the upper Pleistocene and maintained by man through a long history of cutting, cultivation and frequent dry season fires over the last 55,000 year [7].…”
Section: Introduction mentioning
confidence: 99%
“…Woody species composition was analyzed using the Importance Values Index (see (3)), which is the summation of the relative values of frequency, density, and dominance [43]. The Importance Values Index (IVI) describes the floristic structure and composition of the woodlands and has been frequently used in the Miombo systems [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…In general tree biodiversity has not been degraded by the slash-and-burn disturbance, but the time-scale of recovery of defining Miombo species was unclear. In Zambia [29][30][31] have also suggested that though Miombo systems recover relatively fast in terms of species diversity, species composition takes longer to recuperate. In another study in Mozambique, [32] observed that fire and herbivory by elephants are the main drivers of ecosystem structure and composition.…”
Section: Biodiversity In Ecosystems -Linking Structure and Functionmentioning
confidence: 99%